I want 100 dogs - McAnulty, Stacy (Chronicle Books, 2023)
After meeting a dog during a walk, a little girl declares that she wants one hundred dogs, but as her parents point out all the difficulties, she gradually reduces the number--until she gets the one dog she really wants.